KERUGIAN BBM AKIBAT TUNDAAN DAN PANJANG ANTRIAN DI PERSIMPANGAN JALAN RAYA DENGAN REL KERETA API SEBIDANG (Studi Kasus Jalan Hasanudin Semarang) - Ananda, Fina Kurnia; Yaqin, Wafi Ainul; Rizani, Mohammad Debby; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
Due to the high mobility of those passing by and the presence of trains that cross the intersection between the highway and the railroad, also known as level crossings, Jalan Hasanudin experiences heavy traffic during rush hour. Additionally, because of the large volume of train traffic at the Poncol station and the proximity of this intersection to the station, there is frequently a buildup of vehicles at the level crossing on Jalan Hasanudin. As a result, researchers will determine how Jalan Hasanudin Semarang performed. After conducting research, it was discovered that the highest vehicle queue length occurred on Monday, February 27 2023 from Jalan Hasanudin - Imam Bonjol at closing time 16.45 with a queue length of 123 meters and the highest stop delay occurred on Saturday, March 4 2023 from the direction of Jalan Hasanudin - Imam Bonjol with an average stop delay duration of 372.00 seconds. Therefore, the occurrence of long lines led to fuel losses for the drivers; their total gasoline loss over the course of the three research days was IDR 886,550.7. The researchers offer recommendations based on the findings of the research analysis to control street vendors and people near railroad tracks and railroad crossings that result in side barriers and long lines during stop delays, install traffic signs like those that prohibit stopping, prohibit parking, and prohibit raising and lowering passengers on roads, and so that there is no congestion along Jalan Hasanudin and around railroad crossings.